A Site-Specific LoRaWAN Parameters Selection Approach with Multi-Loss Propagation Model - Pandey S.; Kumari P.; Gupta H.P.; Rai D.; Rao S.V. (My University, 2025)
Long Range Wide Area Network (LoRaWAN) emerges as a promising solution due to its impressive communication range. However, achieving this range in real-world environments is influenced by signal absorption and reflection caused by obstructions such as buildings, vegetation, and the ground along the path to the gateway. This challenge is amplified in unknown sites where infrastructure details are unavailable before the deployment of LoRaWAN. To address the aforementioned challenges, the paper proposes an approach to determine and configure the LoRaWAN parameters for a given site. The approach introduces a method that automatically detects obstructions solely using site images, thereby eliminating the need for manual intervention. Subsequently, by employing the concept of a multi-loss propagation model, the approach estimates path loss, taking into account the identified site obstructions along the communication path. Finally, the estimated path loss is utilized to determine site-specific optimal LoRaWAN parameters, aiming to streamline the deployment process and enhance network efficiency. Through extensive experimentation and evaluation in a real-world LoRaWAN deployment, the approach demonstrates significant improvements in communication efficiency and over- all network performance. © 2024 IFIP.